2021
DOI: 10.3390/antiox10030467
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Modified by (−)-Epicatechin and Taxifolin Relevant for the Treatment of Hypertension and Viral Infection: Knowledge from Preclinical Studies

Abstract: Various studies have shown that certain flavonoids, flavonoid-containing plant extracts, and foods can improve human health. Experimental studies showed that flavonoids have the capacity to alter physiological processes as well as cellular and molecular mechanisms associated with their antioxidant properties. An important function of flavonoids was determined in the cardiovascular system, namely their capacity to lower blood pressure and to improve endothelial function. (−)-Epicatechin and taxifolin are two fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 198 publications
0
21
0
Order By: Relevance
“…However, the utilization of acteoside has only been restricted with the symptomatic treatment of the dry cough-associated oral and pharyngeal mucosa irritation [ 53 ]. Irrespective of these compounds, picatechin has been found to possess noticeable antiviral effects, which may be of remarkable importance in the onset of the pandemic situation [ 54 ]. The high effectiveness of this flavonoid is not surprising as it was found that epicatechin inhibits the onset of Mayaro and hepatitis C viral diseases by inhibiting their replication [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the utilization of acteoside has only been restricted with the symptomatic treatment of the dry cough-associated oral and pharyngeal mucosa irritation [ 53 ]. Irrespective of these compounds, picatechin has been found to possess noticeable antiviral effects, which may be of remarkable importance in the onset of the pandemic situation [ 54 ]. The high effectiveness of this flavonoid is not surprising as it was found that epicatechin inhibits the onset of Mayaro and hepatitis C viral diseases by inhibiting their replication [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several natural products are beneficial in eliminating Cd-induced nephrotoxicity [ 11 , 12 , 13 , 14 ]. Taxifolin (TA) is a flavonoid substance present in Siberian larch ( Larix sibirica ) as well as being categorized as a metal-chelating agent [ 15 ]. In addition, it is a non-mutagenic agent and has reduced toxicity compared to other flavonoids [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…When zinc is combined with flavonoid zinc ionophores, the free intracellular zinc concentration increases. Flavonoids, in general, are central dietary supplements, and their notable antiviral activity against several viruses affecting humans may be of particular importance in the ongoing pandemic situation [ 42 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these considerations, we combined here non-toxic dietary supplements composed of zinc picolinate, copper sulfate, and the flavonoids Epigallocatechin-3-gallate (EGCG), Quercetin, Taxifolin (dihydroquercetin), and Naringenin, that act as zinc ionophores and transport zinc cations through the cell membrane [ 26 , 40 , 42 , 43 , 44 , 45 , 46 , 47 ]. The combination effectively inhibited in vitro viral replication in several cell types, including human lung cells.…”
Section: Introductionmentioning
confidence: 99%